American civil justice in a global context: Reforming judicial reform inspired by U.S. models - (:unkn) unknown (My University, 2016)
This article advances three critical observations. First, there is a growing gap between the substantivelegal commitments to justice reform and the persistent failures of judicial systems to satisfy frequentlyarticulated rule-of-law objectives. Second, the internal barriers to reform are so high that purely externalremedies, including those based on U.S. models, are unlikely to succeed. Third, in order to improve thesuccess rate of foreign judicial reform initiatives, the mechanisms, methods, designs, and embeddedtheories of external support for judicial reform require greater explication, comparative evaluation, andcalibrated adaptation to meet the internal needs of reforming communities.